STRTATEGI DAN SOLUSI DAKWAH PADA MASYARAKAT MULTIKULTURAL - Hamdani Khaerul Fikri; Danu wiradaningrat (Mudabbir: Jurnal Manajemen Dakwah, 2020)
da'wah activities are activities inherent in Islam itself, so that in the process of da'wah activities, the seriousness of preachers in determining methods, strategies and messages of da'wah is very important, especially in Indonesian society which is very multicultural. The research addresses the issue of how to model da'wah in multicultural societies by describing its types, trends and identifying possible misunderstandings between individuals and one another or even between one cultural group and another. In this study also presented data and concepts about how the concept of da'wah in a multicultural society that has different characteristics and concepts from a homogeneous society.